67 Effects of Maternal Disposition and Calf Chute Behavior at Weaning on Calf Finishing Performance. (28th November 2020) - Sims, Michael; Beck, Paul A; Stewart, Cyril B; Shelton, Cody; Cauble, Reagan N; Warner, Andrea L
Abstract: Temperament has been reported to impact calf performance. The purpose of this study was to investigate the relationship between maternity disposition and calf temperament at weaning to finishing performance. Maternal disposition at calving and calf chute behavior at weaning data were collected from the University of Arkansas between August 2017 and May 2018. Calves were finished at Oklahoma State University Willard Sparks Research Center between October 2018 and August 2019. Cow behavior was observed at calving and received a disposition score (CDS) that used a 5-point scale where a score of 1 was highly aggressive, and a 5 was apathetic. At weaning, calf weight (WW) and chute behavior (CS) was recorded. Chute behavior at weaning used a 5-point scale; a score of 1 was indicative of a calm exit, and a 5 was aggressive when exiting the chute. Data were analyzed using the GLIMMIX procedure of SAS. Significance was declared at P ≤ 0.05. Calves with CS of 2 at weaning had greater BW both on arrival to feed yard (P < 0.01) and at harvest (P = 0.01) than calves with a CS of 3. Calves from cows with CDS of 3 had greater feedlot arrival weights (P = 0.01) and ADG (P = 0.01) than calves from cows with CDS of 4. This study indicates that cattle with nervous chute behavior (CS = 3) had potentially detrimental effects on performance and can impact overall life-time productivity.